HEALTH EDUCATION ON SEXUALLY TRASMITTED INFECTIONS IN HIGH SCHOOL AT PALEMBANG - M. Izazi Hari Purwoko; Suroso Adi Nugroho; Mutia Devi; Yuli Kurniawati; Nopriyati Nopriyati; Kiki Septiafni; Cayadi Sidarta Antonius; Aryati Fadhila; Ivon Setiawan (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Sexually transmitted infections (STIs) are still being a problem in Indonesia, especially in adolescent. Psychologically, adolescents have a high curiosity but are not accompanied by adequate knowledge of reproductive health, making them at risk for STIs. Educationis one way to overcome this problem. This community empowerment is carried out in the form of online seminars for high school students in Palembang. This activity aims to increase the knowledge of adolescents regarding STIs. The online seminar was preceded by a pre-test. This activity was attended by 341 participants, namely 335 class XII students and 6 teachers. At the end, an evaluation was carried out with a post-test. Statistical analysis found a significant increase in post-education knowledge for both female and male. This community empowerment shows that by providing online seminars on STIs and HIV significantly increased the knowledge of high school adolescents in Palembang.